2009
DOI: 10.1186/1757-1146-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nature and mechanism of foot pain

Abstract: Approximately one-quarter of the population are affected by foot pain at any given time. It is often disabling and can impair mood, behaviour, self-care ability and overall quality of life. Currently, the nature and mechanism underlying many types of foot pain is not clearly understood. Here we comprehensively review the literature on foot pain, with specific reference to its definition, prevalence, aetiology and predictors, classification, measurement and impact. We also discuss the complexities of foot pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 124 publications
(282 reference statements)
3
83
0
1
Order By: Relevance
“…It has been suggested that mechanical stress, which can be represented by high pressures experienced over longer durations (peak pressure and pressuretime integral) is associated with the development of foot pain [28,32]. In fact, our previous research supports this theory whereby older individuals with foot pain displayed significantly higher peak pressure and pressure-time integrals compared to those without foot pain [17].…”
Section: Discussionsupporting
confidence: 64%
“…It has been suggested that mechanical stress, which can be represented by high pressures experienced over longer durations (peak pressure and pressuretime integral) is associated with the development of foot pain [28,32]. In fact, our previous research supports this theory whereby older individuals with foot pain displayed significantly higher peak pressure and pressure-time integrals compared to those without foot pain [17].…”
Section: Discussionsupporting
confidence: 64%
“…Calf pain, ankle pain and foot pain can be due to a large variety of causes (Hawke and Burns, 2009;Choudhary and McNally, 2011). Sural nerve pathology is an uncommon diagnosis (Stickler et al, 2006), but is a condition that may be overlooked as differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Foot pain is common in the general population, with prevalence rates ranging from 10-42% in different populations (Garrow et al 2004, Hill et al 2008, Messing et al 2008, Hawke and Burns 2009). The differences in prevalence rates between studies are probably due to different definitions of pain and prevalence periods (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…today, last month, or last 12 months). Female gender and advancing age have been associated with an increased risk of foot pain (Messing et al 2008, Hawke andBurns 2009) and reduced health-related quality of life has been reported as a consequence (Irving et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation